2011
DOI: 10.1155/2011/232840
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Activated Protein C Resistance, Thrombophilia and Adverse Pregnancy Outcomes: A Study Performed in an Irish Cohort of Pregnant Women

Abstract: The combination of thrombophilia and pregnancy increases the risk of thrombosis and the potential for adverse outcomes during pregnancy. The most significant common inherited risk factor for thrombophilia is activated protein C resistance (APCR), a poor anticoagulant response of APC in haemostasis, which is mainly caused by an inherited single-nucleotide polymorphism (SNP), factor V G1691A (FV Leiden) (FVL), referred as inherited APCR. Changes in the levels of coagulation factors: FV, FVIII, and FIX, and antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
1
7
2
2
Order By: Relevance
“…Nevertheless, the strength of association between recurrent miscarriages and various thrombophilic risk factors contributing to APCR still remains to be elucidated. In this prospective case-control study, the prevalence of APCR in Indian patients with recurrent pregnancy losses was found to be 17.4% which is similar to the observations of most other published studies [2,6,7].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, the strength of association between recurrent miscarriages and various thrombophilic risk factors contributing to APCR still remains to be elucidated. In this prospective case-control study, the prevalence of APCR in Indian patients with recurrent pregnancy losses was found to be 17.4% which is similar to the observations of most other published studies [2,6,7].…”
Section: Discussionsupporting
confidence: 88%
“…Spontaneous abortion may take place in response to an increased coagulation imbalance. Balbas et al found a strong positive correlation of elevated FV and FVIII levels with an acquired APCR phenotype [6]. But we could demonstrate a statistically significant correlation of adverse pregnancy outcomes only with respect to FVIII levels in comparison to normal controls [6,12,13].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…2 Despite the physiological increase in body fluid during the antepartum period as partly reflected by lower serum sodium levels, pregnancy was associated with postoperative VTE. These results suggested the involvement of other factors such as increased procoagulant factors (i.e., fibrinogen, factor VIII, and von Willebrand factor) 18 and reduced anticoagulant factors (i.e., protein C and protein S), 19 as well as venous compression by enlarged uterus. 2 The higher prevalence of emergent surgery among pregnant women may reflect an effort of physicians to avoid surgical complications.…”
mentioning
confidence: 92%
“…No estudo BRATROS, a frequência desse polimorfismo em pacientes com TV foi de 6,6%, enquanto que em indivíduos saudáveis foi de 1,2% (Pieroni et al, 2007) Na gravidez, cerca de 17% da mulheres que apresentavam TEV eram heterozigotas para essa mutação (Middeldorp et al, 2001). Também foi descrito que a presença desse polimorfismo aumenta em cerca de dez vezes o risco de ocorrência de trombose durante a gestação, além de aumentar em cerca de quatro vezes a chance de eventuais complicações obstétricas (Kupferminc et al, 1999;Sedano-Balbás et al, 2011).…”
Section: Polimorfismo No Gene Da Protrombina (F2 20210g>a)unclassified